On the Asset Substitution Problem - Gavish, Bezalel; Kalay, Avner (Journal of Financial and Quantitative Analysis, 1983)
In their seminal paper, Modigliani and Miller [11], [12] demonstrate that if capital markets are perfect and investment policy is held constant, the market value of the firm is independent of its financial decisions. Furthermore, if capital markets are perfect, stockholders have incentive to choose the investment policy which maximizes the market value of the firm (see [6]). Motivated by this assumption, the firm has been viewed as a “black box;” namely, as one homogeneous unit whose clear objective is to maximize its market value. However, in a growing body of recent literature (see [1], [2], [7], [9], [13], and [14]), researchers recognize that the firm in an “imperfect” capital market is a collection of groups whose interests can, and do, conflict. Jensen and Meckling [9] study the roles of three important groups—the owner-manager, the stockholders, and the bondholders—focusing on the potential costs resulting from divergence of interests among them. They provide a theory of optimal capital structure in terms of reducing the costs of these conflicts.